Biophysical monitoring of unphosphorylated STAT3 homodimerization - Mtwebana, Sinethemba Siphokazi (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2018)
Expected release date-April 2020
Keywords: Uncatalogued